EFFECTIVENESS OF DEEP BREATHING RELAXATION TO REDUCE ANXIETY SYMPTOMS IN THE ELDERLY - Maria Helena; Siswanto, Siswanto; Esthi Rahayu (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Old age is a time when the elderly experience aging with new social roles. As they age, the elderly tend to be more susceptible to various psychological problems and health disorders. Psychological disorders that are often experienced by the elderly are anxiety. Anxiety is an emotional state characterized by feelings of tension, worry, and physical symptoms such as increased heart rate and shortness of breath. One technique used to help overcome anxiety in the elderly is deep breathing relaxation. The deep breathing relaxation technique is a fairly practical and easy way for the elderly to do. The purpose of this study was to test the extent to which relaxation techniques with breathing are effective in reducing anxiety in elderly individuals. The method used in this study was a one group pretest - posttest design experiment. Participants in this study were five elderly people at the Werdha Home. Data collection for the study used the Geriatric Anxiety Scale (GAS). The data analyzed using the Wilcoxon signed rank test between the pre-test and post-test showed a significant decrease in anxiety (0.038 <0.05). The elderly experienced a decrease in anxiety from the moderate to mild category. The recommendation given to the elderly is to do deep breathing relaxation independently to help overcome anxiety.